The Rebuilding of Ripon Minster Nave, 1503–22. (1st January 2019) - Werronen, Stephen
Abstract : In 1503, the canons of Ripon Minster initiated a building campaign to replace the church's nave. Through a careful study of the documentary evidence, including sources that have not previously been considered, this article investigates how Ripon's clergy organised and funded the project. It offers a more precise chronology of the works and an assessment of their impact on the use of the church by its parishioners. The article also considers the clergy's motives for rebuilding, proving that the renovation was not a reaction to the old nave's deterioration so much as an initiative to create a grander architectural setting for processions and more space for burial within the church.